Pengembangan Komposit Berbahan Ebonit Dengan Kandungan Sulfur 30 Phr Yang Diperkuat Serat Bambu Untuk Komponen Otomotif - Jaya, Rizky Pradhian Putra Rian, Joko Sedyono, ST., M.Eng., Ph. D., Ir. Bibit Sugito, MT (2016)
This research aimed to know the highest strength of composite from tensile test, izod impact, toughness against bamboo fiber weight variation of 0phr,30phr,50phr ebonite matrix bamboo fiber and knowing composite surface by SEM photo. This research using bamboo fiber material as strengthened and ebonite as matrix. Soaking process of fiber by NaOH 5% during 2 hours. After that mixing process of natural rubber by chemical using press mold machine. Composite Test using ASTM D256-00 for izod impact test, ASTM D638-02 for tensile test, SNI 0778-09 for toughness test and SEM photo. The test result is obtained at composite impact izod value average the highest at composite of bamboo fiber 0phr is 29,400 J/mm², the highest average of tension with bamboo fiber composite weight 50phr is 13,187 N/mm², average highest strain with composite of bamboo fiber weight 0phr is 28,00%,the highest of toughness at composite of bamboo fiber weight 50phr is 96,800 shore scale A. Depend on SEM photo observation conducted, could be concluded that every composite of bamboo fiber show the pore at composite surface due to fiber loss. Keywords: composite, NaOH, bamboo fiber